1998
DOI: 10.1021/es980489k
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Aircraft Deicing/Antiicing Fluid Additives in a Perched Water Monitoring Well at an International Airport

Abstract: Tolyltriazoles have recently been shown to be the primary agents in aircraft deicing/antiicing fluids (ADAFs) responsible for acute Microtox activity. However, little is known about the fate and effect of these compounds in the environment resulting from airport deicing activities. This research communication describes the first evidence that constituents within ADAFs, other than glycols, are present in subsurface water samples from a major North American airport at environmentally significant concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(110 citation statements)
references
References 5 publications
1
107
0
2
Order By: Relevance
“…As shown in Figure 2, the peaks at 9.30, 9.53, 9.72, 9.85, and 10.06 min gave the same accurate mass for the parent ion (m/z = 460. 93225 15 ] − . The characteristic product ions suggested that the first peak (eluting at 9.30 min) was caused by the five-ring isomeric impurity perfluoropropylcyclopentanesulfonate (PFPCPeS) whereas the latter four peaks at 9.53, 9.72, 9.85, and 10.06 min respectively were PFECHS isomers with −SO 3 − and − CF 2 CF 3 in different positions on the six-ring (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As shown in Figure 2, the peaks at 9.30, 9.53, 9.72, 9.85, and 10.06 min gave the same accurate mass for the parent ion (m/z = 460. 93225 15 ] − . The characteristic product ions suggested that the first peak (eluting at 9.30 min) was caused by the five-ring isomeric impurity perfluoropropylcyclopentanesulfonate (PFPCPeS) whereas the latter four peaks at 9.53, 9.72, 9.85, and 10.06 min respectively were PFECHS isomers with −SO 3 − and − CF 2 CF 3 in different positions on the six-ring (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This could have significant implications for these compounds in native aquifers where BT and 5-TTri were reported to be present at mg/L levels (Cancilla et al, 1998(Cancilla et al, , 2003. BT would be more persistent than 5-TTri and CBT in native aquifers.…”
Section: Effects Of Redox Conditions On Degradation Of Bts In Aquifersmentioning
confidence: 99%
“…Benzotriazoles (BTs) including BT and 5-TTri have been widely detected in effluents of wastewater treatment plants around the world at concentrations up to 3.4 μg/L Hollingsworth et al, 2005;Voutsa et al, 2006;Weiss et al, 2006), in sediment and sludge at concentrations up to 198 ng/g (Zhang et al, 2011). Much higher concentrations of up to 126 mg/L for BT and 17 mg/L for 5-TTri have been found in groundwater from airport locations due to its heavy use as an antifogging agent (Cancilla et al, 1998(Cancilla et al, , 2003. Although the acute toxicity of BT and its derivatives (5-TTri and CBT) is very low with reported no-observed effect concentrations (NOEC) being in the mg/L range (Kadar et al, 2010;Pillard et al, 2001), the chronic toxicity of these compounds at such high concentrations may be a concern and requires further investigation (Farre et al, 2008;Harris et al, 2007;Kadar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of BTs and UV filters in surface water Cuderman and Heath, 2007;Kiss and Fries, 2009), ground water (Cancilla et al, 1998(Cancilla et al, , 2003, sediment (Rodil and Moeder, 2008;Zhang et al, 2011), sewage sludge Zhang et al, 2011) and fish (Nagtegaal et al, 1997;Buser et al, 2006) has been reported in literature. From the limited acute toxicity data available in the literature, BTs have relatively low acute toxicity with the reported no-observed-effect-concentrations (NOEC) usually in the mg/L range (Pillard et al, 2001;Kadar et al, 2010).…”
Section: Introductionmentioning
confidence: 98%